Assessing the potential of multi-use to reduce cumulative impacts in the marine environment - Tamis, Jacqueline E.; Jongbloed, Ruud H.; Rozemeijer, Marcel J. C.; Grundlehner, Anne; de Vries, Pepijn; Van Gerven, Annaïk; Jak, Robbert G.; Piet, Gerjan J. (Frontiers in Marine Science, 2024)
The intentional combination of two or more marine activities with the purpose of sharing space, infrastructure, resources and/or operations, referred to as multi-use, is gaining attention as a means to reduce the spatial footprint of human activities but possibly also its ecological footprint. In this study, the Spatial Cumulative Assessment of Impact Risk for Management (SCAIRM) method was adapted and applied to assess whether multi-use can reduce the ecological footprint in terms of the cumulative impacts on the marine ecosystem, by integrating multiple offshore activities in different configurations as compared to these activities separated in space, referred to as single-use. These configurations combine renewable energy, aquaculture, nature restoration and tourism activities, in different combinations. For the sake of this multi-use assessment these activities were subdivided into actions, their allocation in space and time represented in scenarios (e.g. single-use versus multi-use) which were then evaluated in terms of their ecological footprint (i.e. Impact Risk). The main finding is that the calculated Impact Risk in multi-use is often lower than that in single-use and in any case never higher. This study also shows that there is still much to be gained in terms of further reduction in Impact Risk through an optimization of the multi-use design by comparing the scenario based on actual pilots deemed more realistic (i.e. co-existence with limited synergies) with a hypothetical optimal scenario (i.e. multi-functional).